Recognition of Extracellular Bacteria by NLRs and Its Role in the Development of Adaptive Immunity - Ferrand, Jonathan; Ferrero, Richard L. (Frontiers in Immunology, 2013)
Innate immune recognition of bacteria is the first requirement for mounting an effective immune response able to control infection. Over the previous decade, the general paradigm was that extracellular bacteria were only sensed by cell surface-expressed Toll-like receptors (TLRs), whereas cytoplasmic sensors, including members of the Nod-like receptor (NLR) family, were specific to pathogens capable of breaching the host cell membrane. It has become apparent, however, that intracellular innate immune molecules, such as the NLRs, play key roles in the sensing of not only intracellular, but also extracellular bacterial pathogens or their components. In this review, we will discuss the various mechanisms used by bacteria to activate NLR signaling in host cells. These mechanisms include bacterial secretion systems, pore-forming toxins and outer membrane vesicles. We will then focus on the influence of NLR activation on the development of adaptive immune responses in different cell types.